2010
DOI: 10.5120/635-871
|View full text |Cite
|
Sign up to set email alerts
|

Application of an Analytical Hierarchy Process to Prioritize the Factors Affecting ERP Implementation

Abstract: An enterprise resource planning (ERP) system is an integrated software solution, The very fact that about 60-70% of all ERP implementations in organizations around the world end up in a failure or meet their end prematurely calls for a serious look into the factors leading to such results of implementing a powerful integrating tool such as an ERP system, Literature review also shows that the AHP is the preeminent slant among the various methodologies applied to ERP projects in the past for prioritizing the att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Out of this the first two are considered as most important [30] [32]. Vijaya Kumar et al did a study to prioritize the issues affecting ERP system in medium scale fertilizer industry and the following factors were determined: adequate and correct data, training and testing, never run parallel system, conference room pilot, employee retention, customization, and clarity in management objective, external consultant dependency [33].…”
Section: Review Of Literature Of Small and Medium Scale Enterprise (Sme)mentioning
confidence: 99%
“…Out of this the first two are considered as most important [30] [32]. Vijaya Kumar et al did a study to prioritize the issues affecting ERP system in medium scale fertilizer industry and the following factors were determined: adequate and correct data, training and testing, never run parallel system, conference room pilot, employee retention, customization, and clarity in management objective, external consultant dependency [33].…”
Section: Review Of Literature Of Small and Medium Scale Enterprise (Sme)mentioning
confidence: 99%
“…The AHP has been successful applied in various fields [20][21][22][23]. This method has been used frequently for irrigation-related study field [11,[24][25][26][27][28].…”
Section: Multi-criteria Decision Analysismentioning
confidence: 99%
“…As an implication, there were various types and amount of customizations have been done. Even though many studies [13][14][15][16][17][18] suggested the minimum customization to implement ERP successfully, the degree of customization was still unclear.…”
Section: A Erp Customizationmentioning
confidence: 99%
“…A.Yokota and K. Yasuda [9] clarified that the basic version of ERP with no or minimal customization is a category of ERP critical success factors. While M. N. V. Kumar [13] recommended maximum amount of 30% as the limit of customization level to guaranty the success of ERP implementation. However, without an adequate explanation, the extent of customization is still remained unclear.…”
Section: Introductionmentioning
confidence: 99%